'I am (not) Major': anti-fan memes of Paramount Pictures' Ghost in the Shell marketing campaign. Issue 2 (3rd April 2021) - Rendell, James
ABSTRACT: This article examines Paramount Pictures' marketing of its 2017 live-action remake of the 1995 Japanese cult anime Ghost in the Shell and online audiences' responses to it. Analysing the trailers, the article argues that Paramount dually serves existing fans via visually quoting the original film's iconic imagery, and new wider audiences by promoting the remake as an A-list blockbuster via emphasising its lead Scarlett Johansson. Analysing 315 audience-made memes produced by Paramount Pictures' viral marketing 'meme generator' evidences users' responses' anti-fan, anti-orientalist, and anti-whitewashing discourses towards the remake, its star, and Hollywood. In doing so, users perform a range of intersectional identities that read against the remake, whereby memes signify audiences' reading of the trailers and themselves into existence when posting such content online. To conceptualise this, the article uses Homi Bhabha's postcolonial third space, arguing that both memes' meaning and users' identity inscriptions occur interstitially. Resultantly, the article adds to the scarce work on media promotional materials, gives much-needed attention to online image texts, and highlights the saliency of race as part of the intersectional make-up of audience' identities and reading strategies.